2005
DOI: 10.1016/j.eupc.2005.05.013
|View full text |Cite
|
Sign up to set email alerts
|

The coronary sinus conduit function: Anatomical study (relationship to adjacent structures)

Abstract: This study demonstrates an intimate proximity between the coronary sinus, at its beginning and end, and the mitral valve annulus. It also highlights the close relationship between the great cardiac vein, the annulus and the left ventricular free wall. Assessing the same relationship using the currently available imaging techniques should aid in the successful cannulation of the coronary sinus for various cardiological interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
65
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 20 publications
7
65
1
Order By: Relevance
“…[7][8][9] It was noted that the CS may course adjacent to the posterior wall of the left atrium rather than along the MVA. Furthermore, a close relation between the CS and the left circumflex coronary artery (LCX) was detected, which potentially limits the use of percutaneous mitral annuloplasty.…”
Section: Clinical Perspective P 1432mentioning
confidence: 99%
See 2 more Smart Citations
“…[7][8][9] It was noted that the CS may course adjacent to the posterior wall of the left atrium rather than along the MVA. Furthermore, a close relation between the CS and the left circumflex coronary artery (LCX) was detected, which potentially limits the use of percutaneous mitral annuloplasty.…”
Section: Clinical Perspective P 1432mentioning
confidence: 99%
“…4 Previous anatomic studies have reported the relation between the CS, the coronary arteries, and the MVA. 8,9 Maselli et al 9 demonstrated that the LCX coursed between the CS and the MVA in 63.9% of the 61 human hearts that were …”
Section: Cs and Coronary Arteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ortale [19] stated that the diameter of the coronary sinus in adults ranges from 6 to 12 mm. El-Maasarany found that "the coronary sinus was 48.4+5.2 mm long and 9.3+5.3 mm in diameter [20]. Mahmud [21] Table 4.…”
Section: Discussionmentioning
confidence: 99%
“…The latter part of the course of the great cardiac vein, as it left the triangle, lay in close relationship to the left circumflex artery: it passed from below upwards and to the right, then superficial to the artery. Thus the vein had a triple relation to the artery; being proximally inferior, then superficial, and finally superior to the artery [3].…”
Section: Introductionmentioning
confidence: 99%